Idealization XIII : modeling in history - Brzechczyn, Krzysztof, 1963- (Poznań Studies in the Philosophy of the Sciences and the Humanities, 2009)
The book reveals different dimensions of modeling in the historical sciences. Papers collected in the first part (Ontology of the Historical Process) consider different models of historical reality and discuss their status. The second part (Modeling in the Methodology of History) presents various forms of idealization in historiographic research. The papers in the third part (Modeling in the Research Practice) present various models of past reality (e.g. of Poland, Central Europe and the general history of the feudal system) put forward by historians. Other papers consider the status of scientific laws and historical generalizations. The volume will be of interest to those who study analytical philosophy of history, methodology of history and social sciences, social philosophy as well as theory and history of historiography.